Hubungan intensitas belajar dan aktivitas fisik dengan daya tahan kardiorespirasi siswa kelas XII SMAN 9 Mataram - Ahmad Muharriril Ulum; Dadang Warta Chanra Wira Kesumah; Lalu Suprawesta (Jurnal Porkes, 2026)
Low cardiorespiratory endurance among adolescents is a concerning health issue, particularly among 12th-grade students who face high academic pressure and tend to engage in limited physical activity. This study aims to analyze the relationship between study intensity and physical activity and the cardiorespiratory endurance of 12th-grade students at SMAN 9 Mataram. The study used a quantitative correlational approach with a cross-sectional design involving 178 students (mean age 17.2 years; 92 males, 86 females). Data were collected using a Likert-scale study intensity questionnaire (Cronbach’s Alpha = 0.79), the IPAQ-SF, and the MFT. Data analysis employed Spearman’s Rho correlation test and multiple linear regression. The results showed that students had moderate study intensity (38.9 ± 6.3), moderate physical activity (910.0 ± 420.7 MET-min/week), and very low cardiorespiratory endurance (30.1 ± 7.8 ml/kg/min). There was no significant relationship between study intensity and cardiorespiratory endurance (r = -0.085; p = 0.257), but there was a positive and significant relationship between physical activity and cardiorespiratory endurance (r = 0.193; p = 0.010). The combined contribution of the two variables was 28.5% (R² = 0.285; F = 34.981; p < 0.001). These findings support school policies to provide more opportunities for physical activity and encourage students to remain physically active.